2016
DOI: 10.1016/j.ajhg.2016.02.019
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation in Newborns and Maternal Smoking in Pregnancy: Genome-wide Consortium Meta-analysis

Abstract: Epigenetic modifications, including DNA methylation, represent a potential mechanism for environmental impacts on human disease. Maternal smoking in pregnancy remains an important public health problem that impacts child health in a myriad of ways and has potential lifelong consequences. The mechanisms are largely unknown, but epigenetics most likely plays a role. We formed the Pregnancy And Childhood Epigenetics (PACE) consortium and meta-analyzed, across 13 cohorts (n = 6,685), the association between matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

53
837
7
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 757 publications
(917 citation statements)
references
References 84 publications
53
837
7
8
Order By: Relevance
“…Importantly, 6 genes (ENOSF1, HOXB2, IL32, NLRP2, PASK, and TDRD9) exhibited significant CpG-transcript relationships in both adults and children. It is also worth emphasizing that the most significant hit of this study (cg05575921; AHRR) was also the top hit in other studies that have investigated the association between childhood DNA methylation and maternal smoking during pregnancy [31]. In combination, these data suggest that prenatal exposures may influence the epigenetic trajectory to asthma and elicit responses that persist into childhood.…”
Section: Impact Of Prenatal Exposures On the Epigenetic Trajectory Tomentioning
confidence: 64%
See 2 more Smart Citations
“…Importantly, 6 genes (ENOSF1, HOXB2, IL32, NLRP2, PASK, and TDRD9) exhibited significant CpG-transcript relationships in both adults and children. It is also worth emphasizing that the most significant hit of this study (cg05575921; AHRR) was also the top hit in other studies that have investigated the association between childhood DNA methylation and maternal smoking during pregnancy [31]. In combination, these data suggest that prenatal exposures may influence the epigenetic trajectory to asthma and elicit responses that persist into childhood.…”
Section: Impact Of Prenatal Exposures On the Epigenetic Trajectory Tomentioning
confidence: 64%
“…Of the 3,932 CpG sites that remained associated with prenatal smoke exposure after adjusting for cell type, the vast majority (2,965 CpGs) had not been previously reported to be linked to maternal smoking during pregnancy [31]. When these novel CpGs were interrogated for their relationship with gene expression in adults, 254 unique CpGs were found to be significantly associated with the expression of a transcript located within 250 kb.…”
Section: Impact Of Prenatal Exposures On the Epigenetic Trajectory Tomentioning
confidence: 99%
See 1 more Smart Citation
“…In a more recent study, the authors identified numerous loci associated with maternal smoking during pregnancy in a genome-wide consortium meta-analysis and found substantial persistence of such effects in later childhood. 18 Zeilinger et al 19 conducted an epigenomewide study comparing methylation levels among current, former, and never smokers in a population-based panel, and found widespread differences in the degree of site-specific methylation as a function of tobacco smoking. Moreover, they observed that the most significant associations with smoking were for DNA methylation sites in AHRR.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies to date do not differentiate cannabis from tobacco use, despite the fact that cannabis is often smoked together with tobacco, and tobacco has similar effects on infant health. This is problematic because maternal smoking during pregnancy has been consistently shown to influence infant DNA methylation in peripheral tissue and to mediate the association between prenatal exposure (21,22) and infant birth weight (23). Furthermore, a very recent study found that cannabis alone had no independent effect on perinatal outcomes, but augmented the risk associated with tobacco smoking (24).…”
Section: Introductionmentioning
confidence: 99%